Experimentation growth: Evolving trustworthy A/B testing capabilities in online software companies. Issue 12 (5th November 2018) - Fabijan, Aleksander; Dmitriev, Pavel; McFarland, Colin; Vermeer, Lukas; Holmström Olsson, Helena; Bosch, Jan
Abstract: Companies need to know how much value their ideas deliver to customers. One of the most powerful ways to accurately measure this is by conducting online controlled experiments (OCEs). To run experiments, however, companies need to develop strong experimentation practices as well as align their organization and culture to experimentation. The main objective of this paper is to demonstrate how to run OCEs at large scale using the experience of companies that succeeded in scaling. Based on case study research at Microsoft, Booking.com, Skyscanner, and Intuit, we present our main contribution—The Experiment Growth Model. This four‐stage model addresses the seven critical aspects of experimentation and can help companies to transform their organizations into learning laboratories where new ideas can be tested with scientific accuracy. Ultimately, this should lead to better products and services.